The Effect of Entrepreneurial Leadership on MSME Performance in Pasar Lama with Intermediate Variables of Innovation Management and Learning Orientation - Adrian Abiyasa; Louis Utama (International Journal of Application on Economics and Business, 2023)
This study aims to determine the effect of entrepreneurial leadership on the organisational performance of MSMEs in the Pasar Lama area, Tangerang, with innovation management as a mediating variable and learning orientation as a moderating variable. This study used quantitative analysis methods, and data was collected using a Google Forms questionnaire. There are 100 respondents obtained by the research, all of whom are culinary MSME owners in the Pasar Lama area. The research data was processed using the partial least square structural equation modelling (PLS-SEM) method with SmartPLS 3.2.9 software. The results show that in the context of MSMEs in the Pasar Lama area, entrepreneurial leadership has a positive influence on organisational performance, entrepreneurial leadership has a positive effect on innovation management, innovation management has a positive effect on organisational performance, innovation management mediates the relationship between entrepreneurial leadership and organisational performance, and learning orientation did not moderate the relationship between entrepreneurial leadership and organisational performance.